Optimizing simplified growing media to enhance cannabis cultivation - C. Tebdoie; Addi Khana; S. Pajareeyanont; R. Deewatthanawong; P. Kongchinda; N. Montri (International Journal of Agricultural Technology, 2025)
This study evaluated the effects of different growing media on the vegetative growth, chlorophyll content, and inflorescence yield of Cannabis sativa L. ‘Platinum Kush Breath Remix’. A substrate composed of peat moss, perlite, and vermiculite (3:1:1; PM) significantly enhanced plant height, stem diameter, number of nodes, and inflorescence yield. The highest chlorophyll a and total chlorophyll contents were observed in plants grown in a medium comprising coconut coir, perlite, vermiculite, and vermicompost (3:1:1:1; CC1), which was comparable to PM in terms of yield. Both PM and CC1 media significantly outperformed other treatments, indicating their suitability for optimizing C. sativa growth and productivity.
Keywords: Cannabis and Cannabinoid Research; GABA and Rice Research; Plant Parasitism and Resistance